(untitled) (Terr@ Plural, 2022)
This work highlights symbolic territorialities of a ‘terreiro de candomblé’ with fluid spatial dimensions, located in the city of Cajazeiras, Paraíba. The experiences are based on the ethnographic field research conducted between January and April. We outline the morphology of the sacred space represented by geosymbols and their meanings, which refer to the mythology of the African òrìṣà, rescued in the ‘terreiro’. We also describe, from the perspective of Costa’s micro-territoriality (2017), geosymbols outside the ‘terreiro’, eventually accessed by ritual occasion, revealing a symbolic extension of the territory that transgresses previously constructed determinations and constructs new identity spaces.